Modeled dietary impact of industry-wide food and beverage reformulations in the United States and France. Issue 1 (7th June 2017) - Gressier, Mathilde; Privet, Lisa; Mathias, Kevin Clark; Vlassopoulos, Antonis; Vieux, Florent; Masset, Gabriel
ABSTRACT: Background: Food reformulation has been identified as a strategy to improve nutritional intakes; however, little is known about the potential impact of industry-wide reformulations. Objective: The aim of the study was to model the dietary impact of food and beverage reformulation following the Nestlé Nutritional Profiling System (NNPS) standards for children, adolescents, and adults in the United States and France. Design: Dietary intakes of individuals aged ≥4 y were retrieved from nationally representative surveys: the US NHANES 2011–2012 ( n = 7456) and the French Individual and National Survey on Food Consumption ( n = 3330). The composition of all foods and beverages consumed were compared with the NNPS standards for energy, total and saturated fats, sodium, added sugars, protein, fiber, and calcium. Two scenarios were modeled. In the first, the nutrient content of foods and beverages was adjusted to the NNPS standards if they were not met. In the second, products not meeting the standards were replaced by the most nutritionally similar alternative meeting the standards from the same category. Dietary intakes were assessed against local nutrient recommendations, and analyses were stratified by body mass index and socioeconomic status. Results: Scenarios 1 and 2 showed reductions in US adults' mean daily energy (−88 and −225 kcal, respectively), saturated fats (−4.2, −6.9 g), sodium (−406, −324 mg), and added sugars (−29.4, −35.8 g). Similar trends were observed for US youth and in France. The effects on fiber and calcium were limited. In the United States, the social gradient of added sugars intake was attenuated in both scenarios compared with the baseline values. Conclusions: Potential industry-wide reformulation of the food supply could lead to higher compliance with recommendations in both the United States and France, and across all socioeconomic groups. NNPS standards seemed to be especially effective for nutrients consumed in excess.